2022
DOI: 10.1021/acs.joc.1c02263
|View full text |Cite
|
Sign up to set email alerts
|

AgNTf2-Catalyzed Regioselective C–H Alkenylation of N,N-Dialkylanilines with Ynamides

Abstract: Regioselective C–H alkenylation of N,N-dialkylanilines with ynamides was developed using AgNTf2 as a catalyst. This approach represents a facile hydroarylation of ynamides, allowing for the introduction of an alkenyl group exclusively at the para position of aniline derivatives. As a result, a series of 4-alkenyl N,N-dialkyl­anilines were synthesized with excellent regioselectivities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…When AgSbF 6 was examined, the desired 3aa was obtained in 31% yield (Table 1, entry 12). Delightfully, a catalytic amount of AgNTf 2 30 could significantly increase the yield of 3aa to 72% (Table 1, entry 13). A higher reaction temperature resulted in a lower yield (56%) of 3aa (Table 1, entry 14).…”
Section: Resultsmentioning
confidence: 99%
“…When AgSbF 6 was examined, the desired 3aa was obtained in 31% yield (Table 1, entry 12). Delightfully, a catalytic amount of AgNTf 2 30 could significantly increase the yield of 3aa to 72% (Table 1, entry 13). A higher reaction temperature resulted in a lower yield (56%) of 3aa (Table 1, entry 14).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Wei and Si found that when N , N -dialkylanilines were employed as coupling partners, AgNTf 2 was demonstrated to be a better catalyst for the hydroarylation of ynamides and syn -adducts were obtained as the main products (Scheme 18). 45 In the presence of a cationic silver catalyst, the ynamide is first converted into the three-membered silver complex Int-32 , which further undergoes rearrangement to form the silver keteniminium species Int-33 . Subsequently, nucleophilic attack of the para -C atom of the aniline at the α-site of keteniminium yields the α-aryl vinyl silver intermediate.…”
Section: C–c Bond Formationmentioning
confidence: 99%